Development of Web-Based Network Automation Applications Using the Kano Method and Paramiko Library to Simplify the Configuration of Multivendor Network Devices at PT. Digital Vision Nusantara - Andi Andara; Setyawan Widyarto; Rusdah (International Journal of Science and Society, 2023)
Computer network is never separated with configuration which is the main task which has to be done in order to make it work. As we know, to configure some devices either server, switch, or router has several methods if we understand how we communicate with the system. Configuration on routers and switches is currently still conventionally done, which means that to configure routers or switches one by one. This is very inefficient, because if the routers and switches that you want to configure are carried out in hundreds or many routers, then the time required by a network administrator is very long. Therefore, network automation is needed which is a solution to perform these complex and repetitive tasks. This automation can help network administrators to configure networks with many devices at once and minimize errors that occur when configuring in a short time. Repetitive work such as configuration backups, configuration restores, and others can be automated. In this project create a web-based network administration automation application. For application development using the Kano method to identify application requirements, design, build and implement applications, this application utilizes the main library, namely paramiko as a liaison and network automation from servers to network devices using the SSHv2 protocol and the Django framework as a Web developers. For the tests carried out on the application using the Black-Box Testing method. The results of this project application can be used as network automation in terms of configuration of network devices such as router configuration, switch configuration, backup and restore configuration centrally so that they can be managed better. This research was conducted with the aim of knowing the category of each feature in a network automation application, the results of this study obtained priority ospf dynamic routing configuration features that entered Must be with a satisfaction level of 0.4285 if implemented and a disappointment level of -0.4285 if this feature not stated, while for the ip address configuration feature, and the On-Dimensional Login feature with a satisfaction level of 0.5713 and a disappointment level of -0.5713 if this feature is implemented, unlike the PIM routing feature configuration feature and the Indifferent configuration verification feature, which for this feature is not often used.